In vitro Regeneration of Blepharispermum subsessile DC: An Endangered Medicinal Plant of Odisha, India using Cotyledon Explants (Plant Tissue Culture and Biotechnology, 2016)
Multiple shoots were induced on cotyledon explants of in vitro grown seedlings of Blepharispermum subsessile DC, cultured on MS medium supplemented with various combinations and concentrations of BAP, IBA and GA3. The highest regenerative response was observed on medium containing 2.5 mg/l BAP where shoot buds initiated after 12 days of inoculation and about 32 shoots were produced in 30 days time. Addition of GA3 played a key role in leaf expansion and elongation of shoot buds. Addition of the auxin IBA to the induction medium resulted in more callus proliferation rather than shoot bud induction. The elongated shoots were transferred to root induction medium consisting of half strength MS supplemented with IAA, NAA and IBA. Highest rooting response (90%) was recorded in ½ MS supplemented with 1.0 mg/l IAA. Acclimatized plants were maintained in polybags with garden soil for future reintroduction program to their natural habitat.Plant Tissue Cult. & Biotech. 26(2): 255-266, 2016 (December)